Uveitis of spondyloarthritis in Indian subcontinent: a cross sectional study - Ninan, Fini; Mathew, John; Philip, Swetha Sara; John, Deepa; Danda, Debashish; John, Sheeja Susan (International Journal of Advances in Medicine, 2017)
Background: The seronegative spondyloarthritis (SpA) are known to have intimate association with ocular inflammatory disease. While anterior uveitis accounts for 50-92% of all cases of uveitis in the West, it ranges between 28 and 50% in the Asian countries. The aim of this study was to document the clinical profile of uveitis in patients with spondyloarthritis in the Indian subcontinent. Methods: In our hospital based cross sectional study, 166 patients fulfilling Assessment of SpondyloArthritis international Society’ (ASAS) criteria for spondyloarthritis (SpA) were evaluated for evidence and nature of uveitis, including by a slit lamp bio microscope. The characteristics of Uveitis were defined as per the SUN (Standardization of Uveitis Nomenclature) Working Group criteria. 84.3% (140) of the patients were male. Results: Ankylosing spondylitis was the commonest type of spondyloarthritis accounting for 69.3% patients. Evidence of past or present uveitis was found in 16.3% patients. Of the patients with uveitis 96.3% had anterior uveitis. 88.9% of the patients had redness of the eye, and 85.2% reported pain in the eye during an episode of uveitis. Mean duration of musculoskeletal symptoms prior to the diagnosis of SpA was 4.36 years. Of the 24 patients who could recall the course of uveitis 70.8% (17) had recurrent episodes. As a complication of uveitis 18.5% had cataract, and 14.8% had posterior synechiae. 78.3% patients were HLA-B27 positive. 19.2% of HLA-B27 positive patients had uveitis, whereas only 5.6% out of the 36 HLA-B27 negative patients had uveitis. Conclusions: The proportion of patients with uveitis in our study (16.3%) was considerably less than in other studies. The characteristics and profile of uveitis in our cohort of SpA patients from the Indian subcontinent were similar to those previously reported in literature.